Tourism marketing in the age of the consumer - Morrison, Alastair M. (Routledge, Taylor & Francis Group, 2022)
"Tourism Marketing: In the Age of the Consumer offers a fresh and contemporary approach as an introductory textbook on tourism marketing. Six major themes along with the traditional core marketing principles are blended together